Simulation Method for Rubber Compounding under Isothermal Partial Filling Conditions - Guolin Wang; Jingshixiong Wang; Haichao Zhou; Chen Liang (Advances in Polymer Technology)
Rubber mixing is an important link in the production of rubber products. Computational fluid dynamics (CFD) simulation is often used to explore the effect of rubber mixing parameters on rubber mixing effect. Previous CFD-based rubber mixing simulation studies did not consider the impact of using 2D or 3D numerical calculation models on the numerical simulation results. In order to investigate the differences between 2D and 3D numerical computational models in rubber compounding CFD simulation problems, in this paper, we compare and analyze the results obtained from 2D and 3D computational models under different rotational speed conditions to investigate the differences between the models in the numerical simulation of rubber compounding. Three different experimental speeds of the rubber mixer—39, 44, and 49 r/min—were set during the study using 2D and 3D asynchronous rotor models with a speed ratio of 1.15, respectively. The rubber was processed using the Bird–Carreau model. The phase interface between rubber and air was calculated using the volume of fluid (VOF) method. The numerical simulation results of different models show that the rotational speed set to 49 r/min shows the best dispersion distribution effect; the mixing effect and speed change rule obtained by the 2D model are consistent with the results obtained by the 3D model. The performance of the results of the two models is consistent when exploring the numerical simulation of rubber compounding.